PROPRIEDADES ÓPTICAS DE FILMES FINOS DE DIÓXIDO DE TITÂNIO DOPADO COM CROMO E VANÁDIO - CRUZ, Natali Amarante; PATUSSI, Fernando Henrique Galiza; SARACHO, Maria Conceição Miranda; GARCIA, Ana Karoline da Silva; CAVALHEIRO, Alberto Adriano (ANAIS DO ENIC, 2022)
-